The outcome of thrombotic microangiopathy in kidney transplant recipients - Kanza Haq; Shanshan Lin; Alana Dasgupta; Zainab Obaidi; Serena Bagnasco; Umberto Maggiore; Nada Alachkar (BMC Nephrology)
Abstract Background The outcome of kidney transplant recipients with a history of complement-mediated thrombotic microangiopathy (cTMA) and those who develop post-transplant de novo TMA (dnTMA) is largely unknown. Methods We retrospectively studied all kidney transplant recipients with end-stage kidney disease secondary to cTMA and those who developed dnTMA, between Jan 2000 and Dec 2020 in our center. Results We identified 134 patients, 22 with cTMA and 112 had dnTMA. Patients with cTMA were younger at the time of TMA diagnosis (age at diagnosis, 28.9 ± 16.3. vs 46.5 ± 16.0 years; P < 0.001). T-cell mediated rejection, borderline rejection, and calcineurin inhibitor toxicity were more prevalent in the first kidney transplant biopsy (P < 0.05) in the dnTMA group, and antibody-mediated rejection was more prevalent in anytime-biopsy (P = 0.027). After adjusting for potential confounders, cTMA was associated with a sixfold increase in the hazard of transplant failure during the first-year post-transplant (adjusted hazard ratio (aHR): 6.37 [95%CI: 2.17 to18.68; P = 0.001]; the aHR decreased by 0.87 (95% CI: 0.76 to 0.99: P = 0.033) per year elapsed since transplantation. Long-term allograft survival was similar in both groups. Conclusion Post kidney transplant TMA is an important cause of poor allograft survival. More studies are needed to enhance our understanding and management of this disorder.